Could fluoride be considered a genotoxic chemical agent in vivo? A systematic review with meta-analysis - Drummond, Giovana Wagner Branda; Takeshita, Wilton Mitsunari [UNESP]; de Castro, Glaucia Monteiro; dos Santos, Jean Nunes; Cury, Patricia Ramos; Renno, Ana Claudia Muniz; Ribeiro, Daniel Araki (Taylor & Francis, 2023)
The goal of this study was to perform systematic review (SR) to investigate the scientific literature regarding the genotoxicity effects of fluoride exposure (FE). The search of databases used for this study was PubMed/Medline, SCOPUS and Web of Science. The quality of included studies was assessed using the EPHPP (Effective Public Health Practice Project). A total of 20 potentially relevant studies were selected for evaluating the genotoxicity induced by fluoride. Few studies have revealed that FE induces genotoxicity. A total of 14 studies demonstrated negative results whereas 6 studies did not. After reviewing the twenty studies, 1 was classified as weak, 10 were considered moderate and 9 were considered strong, according to the EPHPP. Taken together, it has been established that genotoxicity of fluoride is limited.
Keywords: comet assay; DNA damage; fluoride; Genotoxicity; micronucleus